End-to-end scientific processing in the LIneA Science Portal - Costa, Luiz da; Fausti Neto, Angelo; Ogando, Ricardo; Egeland, Patricia; Maia, Marcio; Peloso, Eduardo del; Souza, Carlos Adean de; Machado, Valter; Singulani, Cristiano (Anais do Brazilian e-Science Workshop (BreSci); 2013: Anais do VII Brazilian e-Science Workshop, 2013)
Dark Energy is one of the greatest mysteries of our time. To better understand that, the Dark Energy Survey (DES) has begun to observe in the end of 2012 a large volume of the universe that will generate a catalog of 400 million galaxies up to redshift ~ 1.4, being a unique sample for many years. Its flow from the telescope to a scientific article must follow a well established path that includes quality assurance, pruning and data sweeping for efficient analysis. This is specially true for DES key projects, when products and results must be vetted by the collaboration before going public. Here we describe the effort to create such an endto-end system in the LIneA Science Portal from catalogs produced by National Center for Supercomputing Applications (NCSA) for DES Collaboration.